Principal’s Public Relation Strategy to Increase Society Belief - Lalu Syauki MS (STAI Hubbulwathan Duri, 2021)
Public relations in this study is a way of interaction and communication between the school and the community in building trust and how the school promotes the school. The purpose of this study is to obtain in-depth information related to the principal's public relations strategy to increase public trust. The research method used a qualitative approach through surveys. Data were taken from observations, interviews and documents. The research participants were teachers, education staff, and the public relations team. Data analysis consisted of data reduction, data presentation, and conclusion making. The results of data analysis show that the principal already has a public relations strategy through media such as websites, social media (Instagram, Facebook, and YouTube channels).